Surface display of Nocardia seriolae HRP1 on Bacillus subtilis and its application as live vaccine for largemouth bass - Fengli Zhang; Ji-Tong Li; Tengyuan Zhang; Xiao Wang; Yuanyuan Yao; Zhigang Zhou (Scientific Reports)
Abstract Micropterus salmoides, adaptable and fast-growing, is a major farmed fish in China. Intensive farming causes multiple diseases, especially hard-to-treat nocardiosis. Vaccines are an effective and safe prevention and control strategy against fish diseases. In this experiment, the highly antigenic HRP1 gene of Nocardia seriolae (N. seriolae) was displayed on the surface of Bacillus subtilis (B. subtilis), and an oral vaccine (HRP1-cotC-B. subtilis) was successfully developed. Immune responses in inoculated fish were tested intermittently over 5 weeks post-administration. Immune protection was evaluated via challenge test. Serological parameters testing showed that the activity of lysozyme and Glutathione Peroxidase (GSH-Px) were significantly increased at the 7th and 21st day post-immunization, and the activity of Alkaline Phosphatase was extremely increased compared to the control. qRT-PCR detection found that oral vaccine could significantly boost the IgM expression of spleen and head-kidney. The expression of spleen major histocompatibility complex (MHC) was enhanced, MHCII at the 7th, 21st day and MHCI at 35th day post-immunization respectively. MHCI has an increasing trend in the head-kidney. CD8 increased in both spleen and head-kidney at different stages of immunization. The inflammatory cytokine il-1β and anti-inflammatory cytokine TGF-β significantly increased in head-kidney at 35th day after immunization. The live bacterial vaccine altered the composition of the intestinal flora, demonstrated a decline in Firmicutes and an increase in Fusobacteria, and a significant decrease in Clostridium replaced by Cetobacterium at the genus level. Largemouth bass immunized with HRP1-cotC-B. subtilis spores exhibited a 18.18% relative survival rate after N. seriolae infection. In conclusion, this study developed a novel oral vaccine against N. seriolae in largemouth bass using B. subtilis spore surface display technology. Oral vaccination improves nonspecific immunity, induces innate and cellular immunity, strengthens bacterial resistance, and increases survival after pathogen infection. This offers an effective strategy for controlling fish nocardiosis in aquaculture.